Catalyst deactivation in the hydrodechlorination of micropollutants. A case of study with neonicotinoid pesticides. (December 2020) - Nieto-Sandoval, Julia; Rodriguez, Mario; Munoz, Macarena; de Pedro, Zahara M.; Casas, Jose A.
Graphical abstract: Highlights: HDC is an effective technology for the removal of neonicotinoid pesticides. The micropollutant nature played a critical role on Pd/Al2 O3 stability. HDC of sulphur-containing compounds led to a fast and strong catalyst deactivation. The suitability of the process was demonstrated in successive HDC-regeneration runs. A deactivation kinetic model successfully described a long-term experiment with THC. Abstract: This work aims to analyse the effectiveness of catalytic hydrodechlorination (HDC) for the degradation of the neonicotinoid pesticides listed in the EU Watch List (Decision 2018/840): acetamiprid (ACT), imidacloprid (IMD), clothianidin (CLT), thiacloprid (THC) and thiamethoxam (THM). With the exception of THC, all neonicotinoid pesticides (1000 μg L −1 ) were completely removed in 30 min at 25 °C, using 0.25 g L −1 of a commercial Pd/Al2 O3 (1 wt. %) catalyst and 50 N mL min −1 H2 flow rate. Strikingly, the micropollutant nature played a critical role on the activity and stability of the catalyst. The sulphur-bearing structures (CLT, THC and THM) showed the slowest degradation rates and led to a progressive deactivation of the catalyst. TEM/EDS and elemental analyses confirmed that the selective interaction of sulphur species on Pd active sites was the main reason for catalyst deactivation. The position of the heteroatom in the pesticide structure also influenced the catalytic deactivation. The catalyst showed a constant activity upon its sequential use in the HDC of ACT and IMD when these compounds were treated individually. Nevertheless, the interaction of the sulphur-containing compounds with the catalyst was remarkably favoured when the five micropollutants were treated in a mixture. A deactivation kinetic model in a long-term experiment was proposed with THC. To overcome catalyst deactivation, a regeneration procedure, based on a simple catalyst washing with a diluted NaClO solution, was developed. The process suitability was finally demonstrated in successive HDC-regeneration runs.